The Relationship of Knowledge with Compliance with Health Protocols for Level III Students of STIKES Santa Elisabeth Medan In 2022 - Ice Septriani Saragih; Friska Sri Handayani Ginting; Amnita Anda Yanti Ginting; Tri Agatha Sherlin (Sean Institute, 2022)
Covid 19 is a health problem that occurs in the world. Spread through droplets (splashes) from the respiratory tract and direct contact, in deciding the spread of Covid 19, the government implements health protocols aimed at preventing the transmission of Covid 19. Knowledge of health protocols is a result obtained from information about actions made to prevent the spread of Covid 19. The purpose of this study is to determine the relationship between knowledge and compliance with health protocols in an effort to prevent the spread of Covid 19 on Level III Students of the STIKES Santa Elisabeth Medan Academic Ners Study Program 2022. The research design uses a correlation design with a cross sectional approach. The number of respondents are 85 level III students of the academic Ners study program with a sampling technique, namely the Total Sampling technique. The data are analyzed using the Sperman rank test. The results of the study obtained a relationship between knowledge and compliance with health protocols on level III students of the academic Ners study program at STIKes Santa Elisabeth Medan with an r of 0.424 and a p-value of 0.000. It is hoped that the results of this study will be used as additional data for subsequent researchers.